Optimized Poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) Production by Moderately Haloalkaliphilic Bacterium Halomonas alkalicola Ext - Martin N. Muigano; Sylvester E. Anami; Justus M. Onguso; Godfrey O. Mauti (International Journal of Polymer Science)
Polyhydroxyalkanoates (PHAs) are biodegradable and biocompatible polymers that are produced by microorganisms as storage materials under limited nutrition and excess carbon. These PHAs have been found to be ideal for replacing synthetic plastics for use in packaging and biomedical applications. In this study, an alkaliphilic and moderately halophilic bacterium Halomonas alkalicola Ext was isolated from Lake Simbi Nyaima in western Kenya and investigated for PHA production. Sudan Black B and Nile Red A staining showed that bacterium had distinct ability for accumulation of PHAs. To optimize PHA production, the bacterium was grown in submerged fermentation under varying culture conditions and different sources and concentrations of carbon and nitrogen. With one-factor-at-a-time (OFTA) approach, optimal PHA yields were obtained after 72 hours at a pH of 10.0, temperature of 35°C, and 2.5% (w/v) NaCl. The bacterium yielded the highest biomass, and PHA amounts on 2% galactose and 0.1% ammonium sulfate as sources of carbon and nitrogen, respectively. A record PHA yield of 0.071 g g-1 with a titer of 1.419±0.09 g/L was achieved from 3.397 g/L of biomass, equivalent to 41.8% PHA content. Using response surface methodology, PHA titer was increased by 1.5% to 1.44 g/L, while PHA content was improved 1.1-fold to 45.57%. Polymer analysis revealed that the extracted PHA was a poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) (3−HB:3−HV=92:8) with two copolymer subunits of 3-hydroxyvaryrate (3-HB) and 3-hydroxybutyrate (3-HV). Halomonas alkalicola Ext attained efficient galactose conversion into PHBV under high salinity and alkalinity conditions.